PERTANGGUNGJAWABAN PIDANA PELAKU YANG DENGAN SENGAJA MENDISTRIBUSIKAN DOKUMEN ELEKTRONIK YANG MEMILIKI MUATAN PENGHINAAN DAN PENCEMARAN NAMA BAIK (Studi Putusan Nomor : 1014/Pid.SUS/2020/PN.Mdn) - Raja Luhut Gandamana; Herlina Manullang; July Esther (Jurnal Visi Eksakta, 2023)
Law as a tool in carrying out social control in this case requires the help of criminology, which is the science that studies crime as widely as possible. In legal provisions in Indonesia, the discussion on age-related insult or defamation is regulated in Article 310 paragraph (1) of the Criminal Code (KUHP), such as the case in Decision Number: 1014/Pid.SUS/2020/PN.Mdn. In this study the method used to collect data by means of literature study. Literature study is a data collection technique by conducting a review study of books, literatures, notes, and reports that have to do with the problem being solved. In this study, the primary legal material for legislation is Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions of the Criminal Code. As for this research, secondary legal material is in the form of publications on law and official articles from print media and electronic media and then arranges them systematically to answer the problems in Decision Study Number 1014/Pid.SUS/2020/PN.Mdn. One of the crimes that often occur in society is insult and defamation through electronic documents or called cybercrime, which is regulated in Article 27 paragraph 3 in conjunction with Article 45 paragraph 3 of Law no. 11 of 2008, although the Criminal Code (KUHP) also regulates insults or defamation, it is regulated in Article 310 paragraph (1) of the Criminal Code (KUHP). It can be seen that nowadays cases of defamation occur through electronic media, according to Polri data from January to September 2021, Polri received at least 2,207 reports of criminal acts using the Electronic Information and Transaction Law. Keywords : Crime, Slander, Indonesia, Electronics.